KONSERVASI AIR TANAH MELALUI PEMBUATAN BIOPORI SEBAGAI UPAYA MENGATASI KEKERINGAN DI DESA JADA BAHRIN KECAMATAN MERAWANG - Anisa Indriawati; Irvani Irvani; Dini Wulansari; Taman Tono; Monika P Handayani (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2015)
Water plays a very important role for humans and the surrounding environment. The amount of water in a particular area can be analyzed through the geology and geohydrology of the area. The lack of water resources in Jada Bahrain Village requires a conservation effort. The conservation efforts made are by making biopores. Making biopores aims to store water reserves so as to overcome drought. The amount of stored water volume can be predicted through the biopore infiltration rate. From the infiltration data obtained, 50 biopore holes in Jada Bahrain Village are estimated to be able to infiltrate water as much as 6286.23 mL/second.